Differences in Perceived Stress, Subjective Well-Being, and Psychosocial Variables by Game Use Type - Goo-Churl Jeong; Kwanhyeong Kim; Bee Kim (Behavioral Sciences)
This study examined the differences in perceived stress, subjective well-being, psychosocial variables, and differences in parents’ parenting styles according to game use type among Korean adults. The study involved 300 participants in their 20s and 30s, a demographic typically associated with frequent gaming. Data were collected through an online survey company, and analyses were conducted using SPSS 25.0, including correlation, cluster, ANOVA, and correspondence analyses. The results showed that the general and adaptive game use groups had significantly lower levels of perceived stress than the maladaptive and risky game use groups. Additionally, the adaptive game use group exhibited significantly higher subjective well-being than the maladaptive game use group. In terms of psychosocial characteristics, except for the general game use group, none of the other groups considered online gaming as addictive. Parenting styles showed significant differences in relation to game use in adulthood. Notably, democratic parenting styles were associated with the general and adaptive game use groups, whereas neglectful parenting styles were linked to the risky game use group. These findings suggest that the risky game use group is as vulnerable to stress as the maladaptive game use group, emphasizing the need for targeted screening and social attention for the risky game use group.